Beatus vir : chrystologiczny Psałterz trzebnicki w Bibliotece Uniwersyteckiej we Wrocławiu (IF 440) wobec egzegezy biblijnej i duchowości cysterskiej XIII stulecia - Tabor, Dariusz (Wydawnictwo Księgarnia Akademicka, 2022)
BEATUS VIR. THE CHRISTOLOGICAL PSALTER IN THE UNIVERSITY LIBRARY IN WROCLAW (IF 440), TOWARDS BIBLICAL EXEGESIS AND CISTERCIAN SPIRITUALITY OF 13TH CENTURY The psalter of Trzebnica (Trebnitz) (Wroclaw, University Library IF 440) has been kept since 1810 in the collection of manuscripts in the University Library of Wroclaw. It has been registered in two catalogues – catalog of J. Ch. Friedriech and catalog of W. Goeber. This codex was an object of researches and studies of many scholars. The first of them was Artur Haseloff, who collocated this manuscript in the Thuringian-Saxon school of book painting of 13th century. Many other scholars contributed to the knowledge about this book. Władysław Podlacha, Feliks Kopera, Erich Kloss, Reiner Maria Libor, Michał Walicki, Alicja Karlowska-Kamzowa, Konstanty Klemens Jażdżewski, Andrzej Wałkówski, Sergiusz Michalski, Gude Suckale Redlefsen, Dariusz Tabor, Romuald Kaczmarek, Anna Sutowicz – these were the researchers, who have taken the study on our psalter. Their research touched especially upon styles of the illuminations, problem of provenance of style, connections with miniature of Saxon-Thuringian school, dependence on the cultural center of Bamberg and connections with the family of Andechs Meranier. Only two researchers studied the paleography of scripture. Dariusz Tabor studied the meaning of miniature and its exegetical and spiritual context.